2019
DOI: 10.1002/cam4.2582
|View full text |Cite
|
Sign up to set email alerts
|

TNPO2 operates downstream of DYNC1I1 and promotes gastric cancer cell proliferation and inhibits apoptosis

Abstract: The import of proteins into the nucleus plays an important role in tumor development. In addition to the classical nuclear import proteins importin‐β and importin‐α, there are many nonclassical nuclear import proteins that include TNPO2. The role of TNPO2 as a nonclassical nuclear import protein in tumors is limited. Our previous studies have shown that DYNC1I1 is a poor prognostic factor for gastric cancer and can promote the proliferation and metastasis of gastric cancer cells. An expression profile chip sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Previous studies confirmed that the lack of DYNC1I1 could lead to the occurrence of neuronal autophagy, which was highly correlated to diseases such as aging and neuronal atrophy [28] . In addition, some studies have reported that the upregulation of DYNC1I1 could inhibit the apoptosis of cancer cells and promote the proliferation and migration of cancer cells [29]. DYNC1I1, the binding subunit of cytoplasmic dynein, could assist the cytoplasmic dynein-mediated transport of P65 to the nucleus, following which P65 could promote the expression of IL-6 and activate the STAT3 phosphorylation to promote the proliferation and metastasis of gastric cancer cells [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies confirmed that the lack of DYNC1I1 could lead to the occurrence of neuronal autophagy, which was highly correlated to diseases such as aging and neuronal atrophy [28] . In addition, some studies have reported that the upregulation of DYNC1I1 could inhibit the apoptosis of cancer cells and promote the proliferation and migration of cancer cells [29]. DYNC1I1, the binding subunit of cytoplasmic dynein, could assist the cytoplasmic dynein-mediated transport of P65 to the nucleus, following which P65 could promote the expression of IL-6 and activate the STAT3 phosphorylation to promote the proliferation and metastasis of gastric cancer cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…DYNC1I1, the binding subunit of cytoplasmic dynein, could assist the cytoplasmic dynein-mediated transport of P65 to the nucleus, following which P65 could promote the expression of IL-6 and activate the STAT3 phosphorylation to promote the proliferation and metastasis of gastric cancer cells [30]. Moreover, DYNC1I1 upregulation could also enhance its downstream TNPO2 expression through SP1 overexpression to promote the proliferation and invasion of gastric cancer cells [29]. This study remarkably found that circCCNB1 silencing induced GPM6A under-expression and DYNC1I1 overexpression to promote the proliferation and invasion of HCC cells by activating the AKT/ERK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Pilot studies have noted DYNC1I1 (dynein cytoplasmic 1 intermediate chain 1) was an adverse factor for the prognosis of patients with liver hepatocellular carcinoma, gastric cancer, colon cancer and glioblastoma ( Gong L.-B. et al, 2019 ; Gong L. et al, 2019 ; Sakthikumar et al, 2020 ; Yin et al, 2020 ; Zhou J. et al, 2021 ). There were no published researches on the ADPRHL1, DYNC1I1, KCNG1 in HNSCC before to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…SiRNA knockdown reduced tumour cell proliferation, colony formation and migration abilities and increased apoptosis in vitro. 26,27 Karyopherin-α1 (KPNA1) expression is elevated in colon cancer and tracks with disease progression. Colon cancer cell proliferation, migration, colony formation and in vivo xenograft tumour growth was impaired by KPNA1 genetic knockout and enhanced by overexpression of the import protein.…”
Section: Other Nuclear Transport Receptors In Cancermentioning
confidence: 99%